The Intentional Aspect of Modern Stylistics - Klushina, Natalia (Respectus Philologicus, 2013)
There are cognitive, communicative, and pragmatic scientific methods in the modern anthropocentric linguistic paradigm. We have created the intentional method as a new integrative linguistic method for studying modern Russian discourse. The main scientific categories of the intentional method include: intention, intentionality, intentional categories, author, and addressee. The intention of the addressee consists of cognitive, communicative, and pragmatic constituents. We can divide intention into cognitive intention, which helps to understand the world, and communicative intention, which organizes communication between addressee and addresser. The intentional method can help to search out creative and subjective factors of human communication. This method can help to understand the nonlinearity and creativity of the communicative processes. The different types of effects of modern communication are analysed in this article. The effect holds not only a perlocutive quality in integral communication; therefore we announce that there are both positive and negative intentional effects in modern communication. Communicative failures are situations when an addressee refuses to carry on a dialogue or experiences indifference to the interlocutor.